Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đặt A=\(\left(\sqrt{2+\sqrt{3}}-\sqrt{3+\sqrt{5}}\right)^2\)
\(\Rightarrow2A=2.\left(\sqrt{2+\sqrt{3}}-\sqrt{3+\sqrt{5}}\right)^2\)
\(=\left(\sqrt{2}\sqrt{2+\sqrt{3}}-\sqrt{2}\sqrt{3+\sqrt{5}}\right)^2\)
\(=\left(\sqrt{4+2\sqrt{3}}-\sqrt{6+2\sqrt{5}}\right)^2\)
\(=\left(\sqrt{3+2\sqrt{3}+1}-\sqrt{5+2\sqrt{5}+1}\right)^2\)
\(=\left(\sqrt{\left(\sqrt{3}+1\right)^2}-\sqrt{\left(\sqrt{5}+1\right)^2}\right)^2\)
\(=\left(\sqrt{3}+1-\sqrt{5}-1\right)^2\)
\(=\left(\sqrt{3}-\sqrt{5}\right)^2\)
\(=8-2\sqrt{15}\Rightarrow A=4-\sqrt{15}\)
Có nhìu cách khác nữa
a) 10n + 1 - 6.10n
= 10n . 10 - 6 . 10n
= 10n . (10 - 6)
= 10n . 4
b) 2n + 3 + 2n + 2 - 2n + 1 + 2n
= 2n . 23 + 2n . 22 - 2n . 2 + 2n . 1
= 2n . (8 + 4 - 2 + 1)
= 2n . 11
M = (a + b)(a2 - ab + b2) + c(a2 + b2) - abc
= - c(a2 - ab + b2) + c(a2 - ab + b2) = 0
2) a) \(x^2-3=\left(x-\sqrt{3}\right)\left(x+\sqrt{3}\right)\)
b) \(x^2-6=\left(x-\sqrt{6}\right).\left(x+\sqrt{6}\right)\)
c) = \(x^2+2x.\sqrt{3}+\left(\sqrt{3}\right)^2=\left(x+\sqrt{3}\right)^2\)
d) = \(x^2-2x\sqrt{5}+\left(\sqrt{5}\right)^2=\left(x-\sqrt{5}\right)^2\)
\(\left(2-\sqrt{2}\right)\left(-5\sqrt{2}\right)-\left(3\sqrt{2}-5\right)^2\)
\(=-10\sqrt{2}+5-18-5\cdot2\cdot3\sqrt{2}+25\)
\(=-10\sqrt{2}-30\sqrt{2}+12\)
\(=12-40\sqrt{2}\)